Geometric Frustration Directs the Self-assembly of Nanoparticles with Crystallized Ligand Bundles - Tomazic, Federico; Muttathukattil, Aswathy; Nabiyan, Afshin; Schacher, Felix; Engel, Michael (Journal of Physical Chemistry B, 2024)
Polymer-grafted nanoparticles are versatile building blocks that self-assemble into a diverse range of mesostructures. Coarse-grained molecular simulations have commonly accompanied experiments by resolving structure formation pathways and predicting phase behavior. Past simulations represented nanoparticles as spheres and the ligands as flexible chains of beads, isotropically tethered to the nanoparticles. Here, we investigate a different minimal coarse-grained model. The model consists of an attractive rod tethered to a repulsive sphere. The motivation of this rod-sphere model is to describe nanospheres with a partially crystallized, stretched polymeric bundle as well as other complex building blocks such as rigid surfactants and end-tethered nanorods. Varying the ratio of sphere size to rod radius stabilizes self-limited clusters and other mesostructures with reduced dimensionality. The complex phase behavior we observe is a consequence of geometric frustration.
CRIS-Team Scopus Importer:2024-11-15